Surface Plasmon Resonance, Formation Mechanism, and Surface Enhanced Raman Spectroscopy of Ag+-Stained Gold Nanoparticles - Athukorale, Sumudu; Leng, Xue; Xu, Joanna Xiuzhu; Perera, Y. Randika; Fitzkee, Nicholas C.; Zhang, Dongmao (Frontiers in Chemistry, 2019)
A series of recent works have demonstrated the spontaneous Ag+ adsorption onto gold surfaces. However, a mechanistic understanding of the Ag+ interactions with gold has been controversial. Reported herein is a systematic study of the Ag+ binding to AuNPs using several in-situ and ex-situ measurement techniques. The time-resolved UV-vis measurements of the AuNP surface plasmonic resonance revealed that the silver adsorption proceeds through two parallel pseudo-first order processes with a time constant of 16(±2) seconds and 1000(±35) seconds respectively. About 95% of the Ag+ adsorption proceeds through the fast adsorption process. The in-situ zeta potential data indicated that this fast Ag+ adsorption is driven primarily by the long-range electrostatic forces that lead to AuNP charge neutralization, while the time-dependent pH data shows that the slow Ag+ binding process involves proton-releasing reactions that must be driven by near-range interactions. These experimental data, together with the ex-situ XPS measurement indicates that adsorbed silver remains cationic, but not as a charged-neutral silver atom proposed by the anti-galvanic reaction mechanism. The surface-enhanced Raman activities of the Ag+-stained AuNPs are slightly higher than that for AuNPs, but significantly lower than that for the silver nanoparticles (AgNPs). The SERS feature of the ligands on the Ag+-stained AuNPs can differ from that on both AuNPs and AgNPs. Besides the new insights to formation mechanism, properties, and applications of the Ag+-stained AuNPs, the experimental methodology presented in this work can also be important for studying nanoparticle interfacial interactions.